FRAKSINASI DAN IDENTIFIKASI SENYAWA TANIN PADA DAUN BELIMBING WULUH (Averrhoa bilimbi L.) - Kamilah Hayati, Elok; Fasyah, A. Ghanaim; Sa’adah, Lailis (Jurnal Kimia (Journal of Chemistry); Vol. 4, No. 2 Juli 2010, 2012)
Fractionation of tannic compound from star fruit leaves was conducted by maseration using acetone : water (7:3), and analytical and preparative thin layer chromatography using a variety of eluents. The isolates obtained were identified using UV-Vis and FT-IR Spectrophotometer. The best eluent for both analytical and preparative TLC was found to be n-butanol : water : acetic acid (4:1:5), which gave three isolates with Rf of 0.53, 0.61, and 0.68. The second isolate (Rf = 0.61), showed a maximum absorption at 331 nm on the UV-Vis spectra. Its IR spectra showed specific absorptions such as OH-assymetric stretch (3372.2 cm-1), aromatic overtone (2071.8 cm-1), and aromatic and benzene stretches at 1625.8 cm-1 and 782.5 cm-1 respectively. These spectra suggest that the tannic compound was either flavan pent-3,6,7,4',5'-ol or flavan pent-3,7,8,4',5'-ol.
Keywords: star fruit leaves (Averrhoa bilimbi L), tannic, thin layer chromatography, UV-Vis Spectrophotometer, and FT-IR Spectrophotometer